TAX-BUDGET POLICY OF LARGE EUROPEAN CITIES - S. V. Bogachov (Финансы: теория и практика)
The article deals with problems concerning the implementation of tax-budget policy pursued in large cities, and the evaluation of its compliance with the principles of the legal, organizational and financial autonomy laid down in the European Charter of Local Self-Government. It was determined that the local self-government is part of the management mechanism that optimally combines the interests of the person and human rights, as well as the interests of the city, region and state. The economic basis of local self-government is the material and financial resources that are owned and managed by the territorial communities. Municipal property, local taxes and fees are the main types of these resources the management of which is realized through the development and implementation of tax-budget policy provided by the local governments. The procedure of assessing the compliance of tax-budget policy of large cities with the principles of financial autonomy is offered. It includes seven steps, in particular: the determination of cities sample; collection of the information on cities’ budgets revenues over five years; calculation of the budget structure indexes (in the context of their own sources and inter-budget transfers): the determination of indexes of the structure of own sources of budget revenues; calculation of budget revenues structure by the most significant items per capita (in comparable monetary units): the generalization of the analysis results; elaboration of recommendations to strengthen the financial autonomy of local governments of cities. The above procedure has been tested using the indexes of cities’ budgets revenues in the Russian Federation, Poland and Ukraine. It was revealed that to manage the revenues of cities’ budgets, all of the above countries complying with the main financial principles of the European Charter of Local Self-Government should take into account the specifics of using the methods and techniques of achieving the financial self-sufficiency. The proposals have been elaborated to strengthen the financial autonomy of local budgets of cities in the Russian Federation by using tax and non-tax sources, including local taxes and fees, and by reducing the share of the state subventions and subsidies. In the future, it is advisable to explore the possibility of identifying and using the additional tax sources to replenish the revenue base of local budgets.